GEREJA UMAT ALLAH SEBAGAI KOMUNIO PARTISIPATIF Refleksi Yuridis-Pastoral atas KHK 1983, Kann.204-207 - Pandego, Higianes Indro (LOGOS, 2020)
The sacrament of baptism makes a person united with Christ and made a member of God’s People. God’s People in the Codex Pius Benedict (Codex 1917) are understood based on ordained and unbaptized. This concept gave rise to a pyramid image of the God’s People. On the contrary, the Codex 1983, which was influenced by the views of the Second Vatican Council, see the People of God in common baptism. Based on the baptism, they assumed the general priesthood duties of Jesus Christ according to their individual. The special conditions were bornf for those who received ordination and thus became sacred ministers who exercised the priesthood of office. Both of the general priesthood and the office of priesthood, are carried out in the communion of the Church. In the community spirit, each member of God’s People participates in the mission of Church received from Christ.